Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/289616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Mixing Ways of Reactants on ZnO Morphology

Abstract: ZnO particles with various morphologies were synthesized by mixing ZnSO4and NaOH solutions at 25°C followed by aging of the suspensions at 40–80°C for 2.0 h, keeping the initial molar ratio of Zn2+to OH−at 1 : 4. ZnO irregular plates were prepared by adding NaOH to ZnSO4whileε-Zn(OH)2rhombic particles were produced using the opposite mixing way. After aging of the slurries at 80°C for 2.0 h, the ZnO plates were kept stable while theε-Zn(OH)2rhombic particles were converted to ZnO whiskers with a length of 1.0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These experimental conditions lead to a formation of particles in a basic solution (final pH>12) whereas in the conventional method crystallization occurs from pH = 3 to 12. Yang et al [29] have also obtained -Zn(OH) 2 when they added the cationic solution to the soda solution. In order to investigate the relationships between ZnO and -Zn(OH) 2 , a part of the slurry was aged 24 hours under vigorous stirring.…”
Section: Hydrolysis and Water Condensation Depend On The Reactant's Cmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental conditions lead to a formation of particles in a basic solution (final pH>12) whereas in the conventional method crystallization occurs from pH = 3 to 12. Yang et al [29] have also obtained -Zn(OH) 2 when they added the cationic solution to the soda solution. In order to investigate the relationships between ZnO and -Zn(OH) 2 , a part of the slurry was aged 24 hours under vigorous stirring.…”
Section: Hydrolysis and Water Condensation Depend On The Reactant's Cmentioning
confidence: 99%
“…Oliveira et al [28] have proposed a precipitation under double-jet conditions to produce micrometric ZnO particles at room temperature. Moreover, recently, Yang et al [29] have reported the obtention of ZnO at 25°C by adding soda to a Zn sulfate solution. However, in many applications ZnO doping is necessary in order to reach the best properties, especially Al doping.…”
Section: Introductionmentioning
confidence: 99%
“…In synthesis I, the precipitation process started immediately when NaOH was added to the Zn 2þ solution. According to the literature, the precipitated white powder corresponds in a first stage to Zn(OH) 2 intermediate, but as soon the pH increases, it becomes ZnO [53,54,55,56]. The general reaction of this synthetic procedure can be described by the following equation:…”
Section: Synthetic Procedures Of Intermediates and Final Productsmentioning
confidence: 99%